Study of beach permeability's influence on solitary wave runup with ISPH method. (December 2021) - Tsurudome, Chiaki; Liang, Dongfang; Shimizu, Yuma; Khayyer, Abbas; Gotoh, Hitoshi
Abstract: Coastal protections, such as dykes, seawalls, breakwaters and natural beaches can often be considered as porous structures. The accurate prediction of wave motion around porous structures is necessary for the effective design of durable coastal protections. Smoothed particle hydrodynamics (SPH) is a meshless particle-based method suitable for the simulations of violent free-surface flows and their interaction with porous structures. In this paper, an incompressible SPH (ISPH) model is applied to the simulations of solitary wave runup on permeable slopes. The apparent density concept is introduced to allow the smooth particles' volume to change when shifting between the pure-fluid region and porous region. The present simulations consider both the triangular beaches with uniform permeability and the solid beaches with overlying porous layers. The study focuses on the influence of permeability on the maximum wave runup heights. New runup laws are proposed, which offer guidelines for the design of porous coastal protections.